Analyzing and Evaluating Business Processes of Supply Chain Management SCM System - Khashiah, Mona Hassan (Journal of Economic, Administrative and Legal Sciences, 2018)
The study aimed to analyze and evaluate business processes of supply chain management system. The study applied case study scenario. The first step in this work is a comprehensive study about the business processes generated from stakeholders of SCM in any business organization. Secondly, this analysis lead to build a model for business processes of SCM. Thirdly, the evaluation process started to discover the degree of weakness in the localized SCM systems. The evaluation criterion is based on the valuable of activities in each business process. The findings of the study showed that the percentages of the activities that don’t add value to the processes are very high. These activities were as follows: 1) the percentage of activities that don’t add value to the purchase goods process is %71, 2) the percentage of activities that don’t add value to the source goods process is %54, 3) the percentage of activities that don’t add value to the replenish stock process is %59, 4) the percentage of activities that don’t add value to the supply finished goods process is %33, and 5) the percentage of activities that don’t add value to the manufacture finished goods process is %50. According to the observation, almost of activities that don’t add value to the processes are communication activities. Communication activities like sending and receiving feedback. The recommended solution to decrease these percentages is using the cloud-based systems for SCM instead of the localized systems for SCM.